The PC Bible. (Berkeley, California : Peachpit Press, 1999)
Personal computers are ever-evolving, with faster processors and new multimedia equipment, not to mention the hundreds of new software programs and applications being developed. Even longtime PC users need a complete and up-to-date reference for a quick spin through an unfamiliar program or a clear explanation of an obscure PC quirk. The PC Bible, Third Edition covers the universe of PC hardware and software. With 75,000 copies sold worldwide, it's a proven readers' favorite.The third edition is fully updated and reworked, with complete coverage of Windows 98 and expanded Internet and networking sections.This blockbuster volume is both an indispensable guide for beginners and a necessary resource for anyone who wants to know what to buy, how to find it, and how to use it.